2020
DOI: 10.18280/jesa.530210
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Logic Based Broken Bar Fault Diagnosis and Behavior Study of Induction Machine

Abstract: This study aims to display fuzzy logic (FL) technique for diagnosis of fault induction machine. This allows monitoring of fuzzy information from different signals to give more accurate judgment on the health of the engine, through using a multi-winding model of induction machine for the simulation of broken bars. This model allows study the influence of defects and appear the behavior of the machine in the different modes of running conditions (healthy and fault). In this work, we focus the application of a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Te fgure indicates that the length of misclassifcation periods is less than 0.7 s; thus, all misclassifcations can be ignored [19,20]. Welch's spectral density analysis in the experimental test to monitor EMA performance [22][23][24][25].…”
Section: Level Of Fault Severity Predictionmentioning
confidence: 99%
“…Te fgure indicates that the length of misclassifcation periods is less than 0.7 s; thus, all misclassifcations can be ignored [19,20]. Welch's spectral density analysis in the experimental test to monitor EMA performance [22][23][24][25].…”
Section: Level Of Fault Severity Predictionmentioning
confidence: 99%
“…A study of asynchronous motor malfunctions has shown that they are classified according to their nature. We distinguish: Bearing faults at 41% [5,6], stator faults at 37% [7,8], rotor faults at 10% [9,10], and other faults at 12% [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…•Data-driven approaches use either a static [16], probabilistic or artificial intelligence model such as artificial neural networks [17][18][19].…”
Section: Introductionmentioning
confidence: 99%